"Jump in the Mud": The Construction of Preschool Children's Sense of Place in Peppa Pig - Wei Xinyang; Huang Xu (Redai dili, 2023)
Research on sense of place in the field of geography is mostly focused on adults, with relatively little research on children's sense of place, ignoring changes in human perceptions, experiences, and attitudes toward the environment from childhood onward. In the field of psychology, child studies tend to focus on the temporal dimension of childhood growth and are relatively inadequate in the spatial dimension, lacking attention to interactions and actual experiences of children with place and space. This study focuses on the human-place relationship of children in daily life against the background of the new turn in cultural geography. Among children, animation, as the main medium through which they perceive the external world, contributes to their cognitive and emotional connections with families, communities, schools, and even cities, and plays an important role in fostering their sense of place. Therefore, based on the perspective of new cultural geography, this study takes Peppa Pig as an example and uses text analysis and other methods to analyze the mechanism through which animation builds children's sense of place by analyzing the scenes and plot elements of the animated series. This study finds that this mechanism contains the following four main dimensions: (1) Aesthetics and familiarity: This dimension includes small-scale and symbolic scene restoration of Peppa Pig; simple, caring, calm, and with the use of warm colors; and childish and awkward drawing styles that meet children's cognition, which can resonate with children and create a sense of familiarity. (2) Sense of belonging: In the social space that the protagonist is exposed to, the animation depicts an ideal family space, including the care of elders and the harmony of family relations; children thus form a sense of "home space" through Paige's "home." Through Paige's "home," children form a sense of belonging to "home." (3) Social bonding and social interaction: In this dimension, the "stress-free" "non-tame" and "low-control" school space implicitly influences children's cognitive and emotional connections to school; in addition, the richness and variety of social scenarios build bridges between children and the real social environment. (4) Nature bonding: The large proportion of nature scenes in the animation effectively compensates for the lack of nature experience of many urban children; the interaction mode between the protagonist and nature panpsychism, embodiment and parent-child interaction enriches their cognition and experience of the natural environment. Overall, through the interactive experience between the protagonist and the place, the animated series "Peppa Pig" shows preschool children the "non-controlled" locality of family space and the "non-regulated" locality of school space, constructing their sense of beauty, familiarity and a sense belonging to the place. In this sense, animation, as a "virtual buffer zone" that expands children's cognitive space, can stimulate their geographical imagination of the real world and is an important medium for developing their sense of place. The interpretation of this mechanism in this study helps to enrich the current research on children's geography and sense of place in China.